Data Dissemination Standards and the Statistical Quality of the IMF's World Economic Outlook Forecasts - Mrkaic, Mico. (Washington, D.C. : International Monetary Fund, 2010)
This paper analyzes the effects of IMF member countries participation in the IMF's Data Standards Initiatives (DSI) on the statistical quality of WEO forecasts. Results show that WEO forecasts for SDDS subscribers are in general better than for GDDS participants and those member countries than do not participate in the DSIs. Policy implications are that the DSI positively affect the statistical quality of forecasts and by extension improve the necessary conditions for multilateral surveillance and the provision of member countries with high quality policy advice.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Forecast Error; Inflation Rate; Right; WP